2009
DOI: 10.1007/s11738-009-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of Cyperus rotundus extract in vitro and ex vitro on banana

Abstract: Allelopathic effects of Cyperus rotundus on banana 'Grande Naine' were studied in vitro as well as ex vitro. To study the allelopathic effects in vitro, the Cyperus extract was added to the multiplication medium during preparation before adjusting the pH. Of the four concentrations, 0.2 and 0.6% decreased the shoot multiplication and shoot length but 1 and 2% extract completely inhibited the shoot multiplication but induced rooting in 50 and 28% shoots, respectively. For the ex vitro studies, the Cyperus extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
9
0
2
Order By: Relevance
“…In general, inhibition in the growth of many weed species in response to different plant extracts is well documented by many investigators (Olofsdotter et al 2002;Duke et al 1998;El-Rokiek et al 2006, 2009. Aqueous extracts of Cyperus were also documented (Alam and Azmi 1991;Porwal and Mundra 1992;Chou Chang and Ming Yang 1992;Quayyum et al 2000;Hamayun et al 2005) and recently by Singh et al (2009). The negative effect of C. rotundus extracts on weed growth is similar to that obtained by Ali (2005).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In general, inhibition in the growth of many weed species in response to different plant extracts is well documented by many investigators (Olofsdotter et al 2002;Duke et al 1998;El-Rokiek et al 2006, 2009. Aqueous extracts of Cyperus were also documented (Alam and Azmi 1991;Porwal and Mundra 1992;Chou Chang and Ming Yang 1992;Quayyum et al 2000;Hamayun et al 2005) and recently by Singh et al (2009). The negative effect of C. rotundus extracts on weed growth is similar to that obtained by Ali (2005).…”
Section: Discussionsupporting
confidence: 64%
“…This weed has been reported to possess high allelopathic activity against crops such as wheat (Alam and Azmi 1991), corn (Porwal and Mundra 1992;Chou Chang and Ming Yang 1992;Hamayun et al 2005), rice (Quayyum et al 2000); banana (Singh et al 2009) and weeds. Ali (2005) reported that mixing ground tubers and leaves of C. rotundus with soil, inhibited barnyard grass and canary grass growth.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in plant growth was earlier reported under allelopathic stress [9][10][11]. Similar reports on the growth of tomato, radish, cucumber and barnyard grass being inhibited via water extract of Lantana camara [12], and inhibition in root initiation, number of roots and root length of hypocotyls of mung bean and pea was observed when treated with leaf extract …”
Section: Resultssupporting
confidence: 84%
“…These include the modification of the soil microbiota [74,104], and enhancement of growth of beneficial microbes in their rhizosphere leading to an establishment of positive feedbacks that can contribute to the decrease of native biodiversity [74]. Allelochemicals are further known to inhibit absorption of ions [105]. Other than allelopathic effects, invasive plants exert competition of resource especially through light [87].…”
Section: Ecological Impactmentioning
confidence: 99%